Identification and validation of genes related to stem cells and telomere maintenance mechanisms as biomarkers for breast cancer - Zhen, Shuang; Huang, Lifeng; Zhu, Qiannan; Chen, Rui; Wang, Jue; Zha, Xiaoming (Frontiers in Immunology, 2025)
BackgroundStem cell-related genes (SCRGs) and telomere maintenance mechanism-related genes (TMMRGs) are pivotal in breast cancer (BC) pathogenesis by facilitating tumor cell proliferation and self-renewal. This study employed integrated transcriptomic and single-cell RNA sequencing (scRNA-seq) analyses to investigate SCRGs and TMMRGs as potential biomarkers for BC and to elucidate their underlying cellular mechanisms.MethodsTotal RNA was extracted from eight BC tumor samples and eight matched adjacent non-tumorous tissues. Differential expression profiling, protein-protein interaction (PPI) network construction, and Molecular Complex Detection (MCODE) were conducted. Biomarker candidates were identified using the least absolute shrinkage and selection operator (LASSO) algorithm, followed by pathway enrichment and immunological analyses. Publicly available scRNA-seq datasets were utilized to delineate BC cell types, with emphasis on cellular subsets exhibiting differential biomarker expression. Heterogeneity, communication, and pseudo-temporal analyses of key cells were examined. Biomarker expression was further validated by reverse transcription-quantitative polymerase chain reaction (RT-qPCR).ResultsJUN, NFKB1, and SP1 were significantly downregulated in BC, potentially modulating disease progression through mechanisms involving extracellular matrix (ECM) remodeling, intracellular signaling, oxidative stress response, and translational regulation. Activated B cells and natural killer (NK) cells demonstrated elevated infiltration levels, accompanied by increased expression of immune checkpoint molecules CD200, CD274, TIGIT, TNFRSF25, and TNFSF15. Nine distinct cellular lineages were annotated, among which mesenchymal cells exhibited pronounced biomarker expression differences and enhanced differentiation potential, designating them as key cellular mediators. Interactions between mesenchymal subpopulations (MSC1, MSC2, MSC3) and other cell types were markedly reduced in BC, despite an overall expansion in mesenchymal cell numbers during disease progression. MSC1 emerged as the predominant subtype. RT-qPCR analyses corroborated the downregulation of JUN, NFKB1, and SP1 in BC tissues.ConclusionJUN, NFKB1, and SP1 were identified as potential biomarkers for BC. These findings highlight the critical role of mesenchymal cells in tumor biology and suggest potential therapeutic targets.